(3GddeYGJ GdHQbjI aj GdfcGJ GdJGQjNjIs - (3eMeO Hf Ydj Hf CMeO Hf Ydj Hf NeGQhjg Hf Whdhf GdOeTbqj GdUGdMj GdMfaj, TeS GdOjf , J (B953 (3g` s
(3ChdgG (B:s
(3GdMeO ddg GdPi CHOY eNdhbGJ GdYhGde s
(3fSNI eUhQI HGdahJZQGa ef NW GdeDdas
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B6 - (3U (B291s
(3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA JGQjN (B- (3bSe (B1 - (3U (B225 ; (3agQS OGQ GdcJH GdeUQjI (B- (3GdLRA (B8 - (3U (B216 s
(3eUOQ GbJfGA GdCUd (B:s
(3GdJjehQjI (B((3eLGejY (B372) s
Keywords: (3GdJGQjNs